Lithium-ion battery recycling pre-processing with electrochemical discharge: Enhancing gas product analysis and pH monitoring - Martina Bruno; Silvia Fiore; Annukka Santasalo-Aarnio (Cleaner Engineering and Technology)
Efficient discharge of Lithium-ion Batteries (LIBs) ensures safe recycling. Electrochemical discharge commonly uses NaCl solutions, causing severe corrosion of battery casing and a release of hazardous gases. This work proposes a novel setup to explore a gaseous product formation during electrochemical discharge processes with low gas quantities, in non-corrosive carbonates solutions (Na2CO3 and K2CO3). Two discharge setups were tested over 120 h: a conventional setup with a single battery completely immersed in the electrolyte; and a novel half-cells setup with two batteries in series, connected through a platinum wire, and partially immersed in the electrolyte. The two setups showed consistent discharge curves and pH trends, without corrosion. After 70 h, the residual voltage of new LIBs (3.8 V) dropped below the safety threshold (2V, 45 ± 1 % of initial voltage for Na2CO3 and 50 % ± 1 % for K2CO3). H2 production was observed during the first 11 h for Na2CO3 (1722 ± 400 ppm/h) and 9 h for K2CO3 (1519 ± 670 ppm/h), with peaks at 2000–2300 ppm/h after 3–5 h while O2 and CO2 production was below the detection limit of the detector (0.1 %-vol for O2, 50 ppm for CO2). pH trends in the aqueous electrolytes (pH increased from 11.5 to 11.6 to 12.5 ± 0.48 pH units after 3 h in Na2CO3, and 12.06 ± 0.06 after 4 h in K2CO3) matched H2 production and the formulation of the hydroxyl ions. The half-cell setup confirmed that H2 release at negative half-cell, increasing the pH of discharge solution. These results presented a safe method for LIBs discharge, avoiding corrosion and hazardous gases release.